Analisis Kinerja Keuangan Perusahaan LQ-45 Go Public di Bursa Efek Indonesia - Waluyo, Agus Joko (Kajian Manajemen dan Bisnis, 2010)
The objective research is to investigate performance of go public companies on Indonesia Stock Exchange. The sources of data are from financial Report of 21 companies from 2004 to 2008. Variables to measure consist of dependent variable (ROE) and independent variables (quick ratio, assets turnover, debt ratio, and competitive industry ratio). Statistical modeling by linear regression with degree of confidence 5% to F test and t test hypothesis is used to measure each variable.